1990
DOI: 10.1128/jvi.64.6.3139-3143.1990
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a possible archetypal JC virus DNA sequence from nonimmunocompromised individuals

Abstract: We molecularly cloned JC polyomavirus DNAs from urine samples of eight nonimmunosuppressed patients and two healthy individuals. The cloned viral DNAs all contained an archetypal regulatory sequence from which various regulatory sequences of JC polyomavirus isolates derived from patients with progressive multifocal leukoencephalopathy could have evolved by deletion and amplification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
152
0
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(166 citation statements)
references
References 15 publications
6
152
0
4
Order By: Relevance
“…These data suggest continuous viral replication in the urinary tract of a strain acquired in childhood, rather than repeated infections with different strains. This continuous excretion may be necessary for JCV transmission within the human population, probably by the oral route, because infection with archetypal JCV strains (the strains present in urine and sewage) [19] is clearly inefficient, as shown by recent in-vitro studies with cell cultures. As for BKV, the differences in the frequency, and above all in the pattern, of excretion suggest that there may be additional mechanisms of transmission other than the oral route; indeed, transplacental and perinatal transmission have been postulated [20].…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest continuous viral replication in the urinary tract of a strain acquired in childhood, rather than repeated infections with different strains. This continuous excretion may be necessary for JCV transmission within the human population, probably by the oral route, because infection with archetypal JCV strains (the strains present in urine and sewage) [19] is clearly inefficient, as shown by recent in-vitro studies with cell cultures. As for BKV, the differences in the frequency, and above all in the pattern, of excretion suggest that there may be additional mechanisms of transmission other than the oral route; indeed, transplacental and perinatal transmission have been postulated [20].…”
Section: Discussionmentioning
confidence: 99%
“…The CY variant had only a single prototype 98-bp unit, but also included the same 23-bp insertion observed in some repeat structures. In addition, CY had a 66-bp insert after nucleotide number 91 that contained sequence comprising almost every downstream insertion seen in repeat structures [81]. Variant GS/K, isolated 2 years earlier in Germany from a PML patient whose kidneys harbored JCV [82], was nearly identical to CY, except for a single base pair deletion in the 66-bp insert.…”
Section: Jcv Genomic Variantsmentioning
confidence: 99%
“…A second classification scheme, based upon differences within the viral transcriptional control region (TCR), has been used to classify BKV into archetype and rearranged forms. Archetype BKV, the form de-tected in urine and thought to circulate in the human population [Yogo et al, 1990;Flaegstad et al, 1991;Yogo et al, 1991], has a TCR structure that lacks extensive duplication of the promoter-enhancer sequences. The rearranged form of BKV may represent a collection of viral variants that arise in an individual after the deletion and duplication of sequences within the archetype TCR [Yogo et al, 1990[Yogo et al, , 1991Tominaga et al, 1992;Ault and Stoner 1993].…”
Section: Introductionmentioning
confidence: 99%
“…Archetype BKV, the form de-tected in urine and thought to circulate in the human population [Yogo et al, 1990;Flaegstad et al, 1991;Yogo et al, 1991], has a TCR structure that lacks extensive duplication of the promoter-enhancer sequences. The rearranged form of BKV may represent a collection of viral variants that arise in an individual after the deletion and duplication of sequences within the archetype TCR [Yogo et al, 1990[Yogo et al, , 1991Tominaga et al, 1992;Ault and Stoner 1993]. The precise mechanism and site of this rearrangement are unknown, however a similar process may occur in a second human polyomavirus, JC virus (JCV), where it has been suggested that an archetype form undergoes active replication and TCR rearrangement at the site of primary infection [Newman and Frisque, 1997].…”
Section: Introductionmentioning
confidence: 99%